Cho P =2x^2/x-3 Q=4/P so sánh Q với1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(B=\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{\left(n-1\right)\cdot n}\)
Ta có:
\(A=\frac{1}{2^2}+\frac{1}{3^2}+...+\frac{1}{n^2}\)\(< \)\(B=\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{\left(n-1\right)\cdot n}\left(1\right)\)
Mà \(B=\frac{1}{1.2}+\frac{1}{2.3}+...+\frac{1}{\left(n-1\right)\cdot n}\)
\(=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+...+\frac{1}{n-1}-\frac{1}{n}\)
\(=1-\frac{1}{n}< 1\left(2\right)\)(đúng. vì \(n\ge2\))
Từ (1) và (2) \(\Rightarrow A< B< 1\Rightarrow A< 1\)
a) \(Q=\frac{x^4-x^2+2x+2}{x^4+x^3+x+1}\)
\(Q=\frac{x^2\left(x^2-1\right)+2\left(x+1\right)}{x^3\left(x+1\right)+\left(x+1\right)}\)
\(Q=\frac{x^2\left(x+1\right)\left(x-1\right)+2\left(x+1\right)}{\left(x+1\right)\left(x^3+1\right)}\)
\(Q=\frac{\left(x+1\right)\left[x^2\left(x-1\right)+2\right]}{\left(x+1\right)\left(x^3+1\right)}\)
\(Q=\frac{x^3-x^2+2}{x^3+1}\)
b) \(Q=\left|Q\right|=\frac{x^3-x^2+2}{x^3+1}\)
A = \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+....+\frac{1}{2^{100}}\)
2A = \(1+\frac{1}{2}+\frac{1}{2^2}+.....+\frac{1}{2^{99}}\)
A = 2A - A = \(1-\frac{1}{2^{100}}<1\)
=> A < 1
Ta có: \(Q=\dfrac{4}{P}\)
\(=4:\dfrac{2x^2}{x-3}\)
\(=4\cdot\dfrac{x-3}{2x^2}\)
\(=\dfrac{2x-6}{x^2}\)
Ta có: \(Q-1=\dfrac{2x-6-x^2}{x^2}=\dfrac{-\left(x^2+2x+6\right)}{x^2}\)
\(=\dfrac{-\left(x^2+2x+1\right)-5}{x^2}\)
\(=\dfrac{-\left(x+1\right)^2-5}{x^2}< 0\)
=> Q<1